Elaboration sites and prepositional meaning construction in English and Polish - Maria Brenda (Research in Language)
Although prepositions are relational linguistic units of modest sizes, they can contribute a variety of different meanings to the constructions they are found in. The paper looks into the notion of e-site, which allows for conceptual elaboration of more schematic entities along the vertical and horizontal dimensions of the human conceptual representation. It argues that e-sites are useful for prepositional meaning description. First, e-sites come into play when schematic TRs and LMs of the preposition are elaborated by more specific conceptual structures, thereby, forming a vertical schematic-specific hierarchy of conceptual structures. Along the horizontal dimension, e-sites are responsible for the integration of the conceptual content of expressions which come together to form constructions. This type of elaboration finds its expression in the typology of languages (satellite- or verb-framed) proposed by Talmy (2000) and elaborated by Slobin (2005).